Drivers of dollar share in foreign exchange reserves - Linda S. Goldberg; Oliver Hannaoui (Federal Reserve Bank of New York, 2024)
The share of U.S. dollar assets in the official foreign exchange reserve portfolios of central banks is sometimes taken as an indicator of dollar status. We show that the observed decline in the aggregate share of U.S. dollar assets does not stem from a systematic shift in currency preferences away from holding dollar assets. Instead, a small group of countries with large foreign exchange reserve balances drive the dollar share decline observed in aggregate statistics. This arises either due to countries conducting monetary policy vis-à-vis the euro or due to preference shifts away from dollars. Regression analysis shows that interest rate differentials between traditional and nontraditional reserve currencies can tilt portfolio composition, particularly in relation to the scale of investment tranches within overall central bank portfolios. Geopolitical distance from the United States and financial sanctions are associated with lower U.S. dollar shares, especially if the primary foreign currency liquidity needs of the central bank are already satisfied.
Keywords: F3; F31; F33; 330; foreign exchange reserves; dollar; liquidity; convenience yields; currency of international debt; foreign exchange reserve management